2021
DOI: 10.13057/biodiv/d220209
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal overlaps of top predators: Dhole, tiger and leopard, and their potential preys in Huai Kha Khaeng Wildlife Sanctuary, Thailand

Abstract: Abstract. Charaspet K, Sukmasuang R, Khoewsree N, Pla-Ard M, Paansri P, Keawdee B, Chanachai Y, Bhumpakphan N. 2021. Spatial and temporal overlaps of top predators: Dhole, tiger and leopard, and their potential prey in Huai Kha Khaeng Wildlife Sanctuary, Thailand. Biodiversitas 22: 580-592. The study of the spatial-temporal overlap of top predators and their prey is important to understand competition among predators and predator-prey relationships so that the viable populations of predators and other animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
(45 reference statements)
1
6
0
Order By: Relevance
“…This study recorded 23 species of ground-dwelling birds from 8 families and 7 orders. The top three recorded were Green Peafowl (Pavo muticus) (8.67%), Red Junglefowl (9.07%), and Red-wattled Lapwing (Vanellus indicus) (1.12%), in descending order of relative abundance (Charaspet et al 2021). The most common species found in Khao Yai National Park from this study were the Siamese Fireback (n: 441), Red Junglefowl (n: 301), and Silver Pheasant, with abundance indices of 10.65%, 7.27%, and 1.84%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study recorded 23 species of ground-dwelling birds from 8 families and 7 orders. The top three recorded were Green Peafowl (Pavo muticus) (8.67%), Red Junglefowl (9.07%), and Red-wattled Lapwing (Vanellus indicus) (1.12%), in descending order of relative abundance (Charaspet et al 2021). The most common species found in Khao Yai National Park from this study were the Siamese Fireback (n: 441), Red Junglefowl (n: 301), and Silver Pheasant, with abundance indices of 10.65%, 7.27%, and 1.84%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, we selected only 3 pheasant species because of the large number found for analysis. The results of long-term studies in the other two conservation areas on Huai Kha Khaeng Wildlife Sanctuary, with 6596 trap days, found 24 species of land-dwelling bird species (Charaspet et al 2021) and Khao Ang Rue Nai Wildlife Sanctuary, with 4463 trap nights, found 11 species of the landdwelling bird species (Sukmasuang et al 2020), including 3 areas with 50 land-dwelling bird species living on the forest floor, confirmed to indicate the abundance of landdwelling bird species of Khao Yai National Park is the most diverse as detailed in table 7. Comparing to the study by Zou et al (2019), who studied the abundance of ground birds in the Nanling Mountains of the Republic of China, reported a total of 44 bird species and 26 mammal species identified using data from 24 camera traps and 6786 photos.…”
Section: Discussionmentioning
confidence: 99%
“…Within the Thung Yai Naresuan Wildlife Sanctuary, this project focused on a 925 km 2 study area in the north and eastern half of Thung Yai Naresuan East (TYNE; Figure 1 ). We compared our data with the findings from an adjacent study [ 20 ] in the northwest portion of the Huai Kha Khaeng (HKK) Wildlife Sanctuary, just to the east of TYNE. The centers of the two camera arrays were about 35 km apart.…”
Section: Methodsmentioning
confidence: 99%
“…The centers of the two camera arrays were about 35 km apart. Study area elevations in TYNE averaged 967 m (range 664–1335) vs. the average elevations of 200–500 m (range 160–1687 m) in HKK [ 20 ], As a consequence of these elevational differences, the TYNE study area likely has a higher proportion of dry evergreen forest vs. more mixed deciduous forest with bamboo in HKK. In addition, there is more protection and less habitat alteration by humans within HKK.…”
Section: Methodsmentioning
confidence: 99%
“…The study of predators is important to understand competition among predators and predator-prey relationships so that the viable populations of predators and herbivorous, insectivorous mammals can be sustained (Charaspet et al 2021). The number of predator species also affects their competitive activity (Lucherini et al 2009).…”
Section: Introductionmentioning
confidence: 99%